Dissimilar materials laser welding characteristics of stainless steel and titanium alloy - Mohid, Zazuli; Liman, M.A.; Rahman, M. R. A.; Rafai, Noor Hakim (Trans Tech Publications, 2014)
Welding parameters are directly influenced by the work material properties. Thermal properties such as thermal conductivity and melting point are very important to estimate the range of power required and the allowable scanning speed. However, when two or more different materials are involved, modifying lasing parameters are not enough to counter the problems such as imbalance melting region and weak adhesion of contact surface. To counter this problem, the characteristics of welding beads formation for both materials need to be clarified. In this study, comparison of welding beads constructed using the same scanning parameters were done to understand the different and similarity of melted region for the both materials. Actual welding of the both materials were done under different offset distance to obtain a balanced melting area and well mixed melting region.